PENYULUHAN HUKUM DAMPAK MEDIA SOSIAL BAGI REMAJA - Tri Murti Lubis; Syarifah Lisa Andriati; Detania Sukarja (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Teenagers are the next generation of the nation that must continously be fostered to shape their identity and personality in accordance with Indonesian values. Various problems related to adolescents both as objects and as subjects have emerged with the development of information technology. Information technology has developed since the discovery and development of Science in the field of information and communication, starting from the development of communication system to communication equipment and direct and interactive communication tools. Social media is like a double-edged knife. If used wisely, selectively and responsibly, various social networking sites can be useful and beneficial. However, if used irresponsibly, social media can bring bad results, even legal problems. Therefore, social media users should be more careful in using the platform. The growing usage of social media among teenagers may bring negative impact if not addressed wisely due to teenagers’ vulnerability. The lack of legal knowledge on the use of social media may also cause adolescents becoming perpetrators and/or victims of social media.